PROMOSI DESA WISATA PENGLIPURAN PASCA PANDEMI COVID–19 MELALUI FESTIVAL BUDAYA STUDI KASUS: PENGLIPURAN VILLAGE FESTIVAL IX - Ni Nyoman Arini; I Made Bayu Wisnawa; Putu Guntur Pramana Putra; I Nengah Sandi Artha Putra (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2023)
Penglipuran Village Festival is a cultural festival held as a form of community commitment to preserve traditions and culture in Penglipuran Village. This study analyzes the event marketing process in organizing Penglipuran Village Festival IX and how Penglipuran Village Festival IX became a promotional medium for Penglipuran Tourism Village after the Covid-19 pandemic. This study used qualitative descriptive analysis. Data collection techniques carried out in this study are observation, interviews and documentation. Data is analyzed based on the event marketing process and 7P marketing mix, namely product, price, place, promotion, process, people, and physical evidence. The results of this study show that the implementation of the Penglipuran Village Festival IX event is in accordance with the event marketing process based on the model of Lynn Van Der Wagen (2010). 7P as an element of the marketing mix has also been fulfilled in Penglipuran Village Festival IX. The main target of Penglipuran Village Festival IX is foreign tourists and quality domestic tourists. The presence of the Penglipuran Village Festival IX event with various interesting programs can be a turning point in tourism recovery after the Covid-19 pandemic.